Experiments on cold-formed ferritic stainless steel slender sections. (June 2015) - Bock, M.; Arrayago, I.; Real, E.
Abstract: The usage of stainless steel in construction has been increasing owing to its corrosion resistance, aesthetic appearance and favourable mechanical properties. The most common stainless steel grades used for structural applications are austenitic steels. The main drawback of these grades relies on their nickel content (around 8–10%), resulting in a relatively high initial material cost. Other stainless steel grades with lower nickel content such as the ferritic steels offer the benefits of stainless steels in terms of functional qualities and design but within a limited cost frame. Hence, ferritic stainless steels may be a viable alternative for structural applications. Given the fact that little experimental information on ferritic stainless steels is currently available, the purpose of this investigation is to report a series of material and cross-section tests on ferritic grade EN 1.4003 (similar to 3Cr12) stainless steel square and rectangular hollow sections to enable a better understanding of their material response and structural performance. Four different cross-section geometries have been tested under pure compression and in-plane bending. Measurements of geometric imperfections and material properties are also presented. The obtained test results are used to assess the adequacy of the slenderness limits and effective width formula given in EN 1993-1-4 to ferritic stainless steels, those proposed by Gardner and Theofanous and Zhou et al. design approach. Highlights: Experimental study of ferritic stainless steel stub columns and beams Local buckling of cross-sections with different aspect ratios Applicability of various design methods for cross-section design to ferritic stainless steel Design recommendations